The Influence of Parental Mediation to Perception of Television Positive Effect On Childrens - Udyahitani Secundaputeri .; Drs. Hj. Sri Widowati H., MS (Interaksi Online, 2016)
Television is one of the media used by indonesians as a source of information, entertainment, and education because it is easily to absorb messages that delivered so television be an effective instrument to influence the public perceptions especially childrens. Perception of television positive effect in children is very important to be developed because can help children as active audience to distinguish between impressions a positive and negative for children. Although the children was said to be active audience, but it cannot be denied that children are still unstable to sorting of bad things and good things that is in impressions by television. So is needed parents mediation in supervising child while watching television to continue assist develop perception of television positive effect in children. This research aims to understand the influence of parental mediation against perception the positive effects of television on children. To answer these problems used parental mediation theory. The population in this research was children aged 10 to 12 years in semarang city that within 1 last month got parental mediation when watching television from their parents in any form either active mediation, restrictive mediation, nor coviewing mediation. Respondents who taken are 120 respondents using nonprobability techniques of sampling. Data obtained analyzed using the eligibility test, classical assumptions test, and continued with multivariate linear regression analysis with help by SPSS V. 16.0 application program. The first hypothesis test result indicated that the restrictive mediation variable (X1) does not significantly influential the perception of television positive effect on childrens (Y). The second hypothesis shows that the active mediation variable (X2) positively influential and very significant (Sig.=0,004) to perception of television positive effect on childrens (Y). The higher childs get active mediation from parents the higher perception of television positive effect on child. The third hypothesis test shows that the coviewing mediation variable (X3) does not significantly influential the perception of television positive effect on children (Y). The coefficients determined showing that the R square value is 0,131 which means that parental mediation contributes influence by 13% to perception of the television positive effects in children.